Neutrophil extracellular traps are increased in cancer patients but does not associate with venous thrombosis - Oklu, Rahmi; Sheth, Rahul A.; Wong, Keith H. K.; Jahromi, Amin H.; Albadawi, Hassan (Cardiovascular Diagnosis and Therapy, 2017)
Background: A single center, prospective tissue-based study was conducted to investigate an association between neutrophil extracellular traps (NETs) and venous thromboembolic disease in patients with malignancy. Methods: Plasma was collected from 65 patients in which 27 were cancer patients and 38 were agematched non-cancer patients. Plasma NETs, circulating free DNA (cfDNA), DNase-1, endonuclease-G, endonuclease activity and thrombin-antithrombin III (TAT) complex levels was quantified. Laboratory values were also compared. Additionally, NETs detection and quantification was performed with fluorescent immunohistochemistry (IHC) in tissue-banked tumor sections and fresh human venous thrombus derived from cancer patients. Results: Plasma samples from cancer patients contained higher levels of nucleosomes (P=0.0009) and cfDNA (P=0.0008) compared to the non-cancer group. Western blot analysis revealed significantly lower DNase-1 protein levels (P=0.016) that paralleled lower nuclease activity (P=0.03) in plasma samples from cancer patients compared to non-cancer patients. Thrombus tissue from cancer patients and tumor tissue from liver and lung cancer also showed marked levels of NETs. However, increased levels of NETs in cancer patients did not correlate with TAT complex activation or prevalence of venous thrombosis in cancer patients. Conclusions: Further studies are warranted to determine the role of NETs as a procoagulant in human thrombosis.